The effect of a psychological approach on Serotonin and Cortisol hormones for young volleyball players - Abbas, A. H.; Azeez, A. A. (Journal of Optoelectronics Laser, 2022)
The purpose of this paper is to identify the effect of a psychological approach on the hormones serotonin and cortisol for young volleyball players. The researchers used the experimental method because it is the appropriate method to solve the research problem and achieve its objectives , represented by the players of the Al-Daghara Youth Club in volleyball for the sports season 2020-2021, where they numbered (14) players and in a simple random way (lottery) they were divided into two groups (control - experimental) with (7) players for each group. As for the variables, they are the psychological approach based on scientific foundations and principles that directly contribute to the player getting the best physical, skill and scheming level, and serotonin is one of the neurotransmitters that plays an important role in regulating human mood and mental health by increasing neurotrophic (the happiness hormone), and cortisol Which is secreted by the body from the adrenal gland in response to the body`s exposure to stress, whether psychological or physical and mental visualization is a mental means through which perceptions of previous experiences or new perceptions can be formed for the purpose of mental preparation for performance. The most important conclusion is that the applied psychological approach led to an increase in serotonin and a decrease in cortisol at a near-normal level, which helped volleyball players in improving mood, reducing negative psychological impact and spread morale in the practice of training units and competitions well, which enhanced physical and physiological health and helped attention the ability to choose the appropriate tactics.